Does the implementation of UHC reforms foster greater equality in health spending?: evidence from a benefit incidence analysis in Burkina Faso - De Allegri, Manuela; Rudasingwa, Martin; Yeboah, Edmund; Bonnet, Emmanuel; Somé, Paul André; Ridde, Valéry (BMJ global health, 2021)
Introduction Burkina Faso is one among many countries in sub-Saharan Africa having invested in Universal Health Coverage (UHC) policies, with a number of studies have evaluated their impacts and equity impacts. Still, no evidence exists on how the distributional incidence of health spending has changed in relation to their implementation. Our study assesses changes in the distributional incidence of public and overall health spending in Burkina Faso in relation to the implementation of UHC policies. - Methods We combined National Health Accounts data and household survey data to conduct a series of Benefit Incidence Analyses. We captured the distribution of public and overall health spending at three time points. We conducted separate analyses for maternal and curative services and estimated the distribution of health spending separately for different care levels. - Results Inequalities in the distribution of both public and overall spending decreased significantly over time, following the implementation of UHC policies. Pooling data on curative services across all care levels, the concentration index (CI) for public spending decreased from 0.119 (SE 0.013) in 2009 to −0.024 (SE 0.014) in 2017, while the CI for overall spending decreased from 0.222 (SE 0.032) in 2009 to 0.105 (SE 0.025) in 2017. Pooling data on institutional deliveries across all care levels, the CI for public spending decreased from 0.199 (SE 0.029) in 2003 to 0.013 (SE 0.002) in 2017, while the CI for overall spending decreased from 0.242 (SE 0.032) in 2003 to 0.062 (SE 0.016) in 2017. Persistent inequalities were greater at higher care levels for both curative and institutional delivery services. - Conclusion Our findings suggest that the implementation of UHC in Burkina Faso has favoured a more equitable distribution of health spending. Nonetheless, additional action is urgently needed to overcome remaining barriers to access, especially among the very poor, further enhancing equality.